Joint Costs in the Chemical Industry - Kreps, T. J. (Quarterly Journal of Economics, 1930)
I. Joint Costs a phenomenon of production; costs as flows; joint means joined, 416. — II. Joint costs with invariable proportions, 419. — Bases of cost apportionment, 420. — Relative demand schedules, 421. — Method of addition and subtraction, 424. — Arbitrary methods of allocation, 425. — Repercussions on the structure of industry, 427. — Cartellization, 429.—Vertical and lateral integration, 431. — III. Joint costs with variable proportions, 433. — Manipulating the variables of chemical equilibria, 436. — By varying concentration, 437. — Temperature, 436. — Pressure, 440. — And state of aggregation of the components, 441. — Mathematical predictability of variation, 444. — Research laboratory as systematizer of march of invention and nerve centre of control of production and marketing, 445. — IV. Nature and scope of joint costs, 448. — Element of technological compulsion vs. element of profit-maximizing variability, 449. — The problem of valuation, 450. — All the factors may vary discontinuously, 452. — Joint costs and overhead costs, 455; and decreasing costs, 459. — Conclusion, 460.